Molecular mechanism of seed dormancy release induced by fluridone compared with cod stratification in Notopterygium incisum - Aihua, Li (BMC Plant Biol, 2018)
BACKGROUND: Notopterygium incisum is an important Chinese medicinal plant. Its mature seeds have underdeveloped embryos and are physiological dormant. We found the seeds with full developed embryos can germinate after treated by fluridone (FL), an inhibitor of abscisic acid (ABA). In order to understand the molecular mechanisms underlying seed dormancy release by FL, we compared the transcriptomic changes in dormancy release induced by two different methods, FL and cold stratification (CS) in N. incisum. We further analyzed the gene expression patterns involved in seed germination and dormancy using quantitative reverse-transcription PCR. RESULTS: RNA-sequence analysis revealed more dramatic changes in the transcriptomes of FL than those in CS, particularly for genes involved in the biosynthesis and regulation of gibberellins (GAs) and ABA. The down-regulation of ABA biosynthesis genes and the dramatic up-regulation of NiCYP707As, an ABA catabolic gene, contributed to the reduced ABA levels in FL. The increased GA(3) levels in CS-treated seeds were due to the up-regulation of NiGA3OX. Both NiABI5 (a positive ABA regulator) and NiGAI (a negative regulator of GA) were down-regulated in FL and CS. The upregulation of strigolactones (SLs; the metabolites with the same precursor as ABA) biosynthesis and regulatory genes in both FL- and CS-treated seeds indicates that SLs contribute positively to seed dormancy release in N. incisum. CONCLUSIONS: Our results indicated that FL- and CS-seed dormancy release possibly depends on two totally different mechanisms: alleviation of the effects of ABA and potentiation of the effects of GA, respectively. However, NiABI5 and NiGAI probably function as common factors integrating the effects of ABA and GA on seed dormancy release. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12870-018-1333-2) contains supplementary material, which is available to authorized users.